Duyar Barisal shilpakala academy as the gateway of Barisal city: Band road, Barisal - Mostafa, Sharmeen (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2016.